(1014) The Application of Linear Programming Models for Planning the Optimal Structure of Foreign Trade تطبيق نماذج البرمجة الخطية لتخطيط الهيكل الأمثل للتجارة الخارجية - Dieter Schumeister (INP., 2020)
Foreign trade planning aims to optimize the structure of exports and imports, as well as their regional distribution, to maximize foreign exchange earnings and improve trade efficiency. This paper explores the use of mathematical models as auxiliary tools for developing optimal trade plans that align with both short-term and long-term objectives while considering internal and external economic conditions. Various programming techniques, including linear, nonlinear, and dynamic programming, have been developed for economic planning. Among them, linear programming has proven to be the most advanced and widely applied method, particularly in socialist economies.